Supported housing for adults with psychiatric disabilities: How tenants confront the problem of loneliness. (19th October 2017) - Piat, Myra; Sabetti, Judith; Padgett, Deborah
Abstract: The objective of this study was to examine the experience of loneliness among people with psychiatric disabilities after moving from custodial housing, including group homes, boarding homes, and family‐type residences to independent, supported apartments in the community. Qualitative research methods guided by a naturalistic/constructivist framework were used. Data collection occurred between May 2014 and July 2015 and consisted of individual semi‐structured interviews with 24 tenants residing in five supported housing sites across three Canadian provinces; interviews were also conducted with a designated family member for each tenant and with their service providers. Group interviews were conducted with housing workers in the five housing sites. The interviews were transcribed verbatim, codes generated and a thematic analysis undertaken using a constructivist approach. Results showed that for most tenants living in independent apartments with support loneliness was not a serious problem or was an issue that could be overcome. Most study participants viewed supported housing as preferable to custodial housing and as a normalising experience that facilitated community integration. While housing conditions, particularly those associated with congregate housing, sometimes helped attenuate loneliness among tenants, managing loneliness was primarily contingent on the ability of individuals to develop and maintain social connections, as well as on family involvement.